The Chitosan-Sodium Alginate Submicro Particles Loading Herbal of Ethanolic Exract of Leaves Senna Alata. L for Curing of Bacterial Infection on Skin - Mardiyanto Mardiyanto; Indah Sholihah; Thio Gunawan Jaya (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2020)
Abstract Mardiyanto 1*, Indah Solihah 1, and Thio Gunawan Jaya 1 1Department of Pharmacy Faculty of Science Sriwijaya University *Corresponding Author : mardiyantoUNSRI@gmail.com This research was performed to detect the activity of the optimum formula of chitosan and sodium alginate submicro particles loading of the ethanol extract of leaves ketepeng cina (Senna alata L.) to P. acne growth. Submicro manufactured particles was used three variations of the formula from three of volume used of calcium chloride (CaCl2): 20, 40, and 100 mL based on ionic gelation method. The results obtained of %EE in formulas 1, 2 and 3 were 78.56%, 81.71%, and 77.48%. Formula 2 with a value of % EE of 81.71% was used as an optimum formula which indicates that the particles are well protected by chitosan and sodium alginate polymers so as to prevent particle damage during the homogenization process. The results of the diameter measurements showed that the optimal formula enters in the submicro particle range with the value obtained is 525,9455 nm. The submicro formula of chitosan alginate particles loading the ketepeng cina leaf ethanol extract was barely homogeneous which based on the results obtained by the PSA was 0.433 of PDI. The zeta potential value was +3.5 mV. The results of X-ray diffraction analysis or X ̶ Ray Diffraction produce a pattern shaped amorph with the resulting peak does not have a wide distance and pattern. In vivo testing using ketepeng cina leaf extract as submicro was decreased the P. acne lesion faster than using only ketepeng cina leaf extract because the submicro particle preparation has a small particle that is below to 600 nm making it easier to penetrate the skin pores to reach the target. The results of the analysis of the curing of many lesions on the skin of mice have a significance value of homogeneity. The one-way ANOVA test of < 0.05 was a significant effect of the test group on the decreasing in the number of lesions on the skin of the mouse.